External financing of local governments’ expenditure in the rural areas in Poland - Daniłowska, Alina (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2011)
The role of repayable sources in financing local governments’ expenditure in rural areas in Poland was examined. The analyses showed that during years 2005-2009 the expenditure of local governments in rural areas was rising. An especially high increase was observed in 2009. The shares of the investment expenditure in total expenditure were at 20% for 2005-2008 but in 2009 it rose noticeably. The local governments use credits, loans and municipal bonds for financing expenditure. Except for 2009, the ‘new’ credits and loans financed mainly repayment of ‘old credits’, only in 2009 less than 50% of ‘new credits’ value was used for repaying old debts. The debt of local governments in rural areas rose quickly but in examined years the payments of interest were not a problem and took less than 1% of budget incomes. In the future, it can change because of the expected increase of debts and, moreover, the interest rates could rise noticeably